Combination Effect of Engineered Endolysin EC340 With Antibiotics - Hong, Hye-Won; Kim, Young Deuk; Jang, Jaeyeon; Kim, Min Soo; Song, Miryoung; Myung, Heejoon (Frontiers in Microbiology, 2022)
Bacteriophage lysins, or endolysins, are hydrolases of the peptidoglycan cell wall that are used when phages burst out after multiplication inside bacteria. When applied from the outside of Gram-negative bacteria as recombinant proteins, they cannot easily reach the cell wall due to the presence of an outer membrane. In this study, an endolysin obtained from phage PBEC131 infecting Escherichia coli was engineered for improved outer membrane permeability and increased activity against Gram-negative bacteria. The engineered endolysin, LNT113, was tested for potential synergistic effects with standard-of-care antibiotics. A synergistic effect was demonstrated with colistin, while an additive effect was demonstrated with meropenem, tigecycline, chloramphenicol, azithromycin, and ciprofloxacin. Neither ceftazidime nor kanamycin showed any synergy or additive effects with LNT113 endolysin. Moreover, synergy and additive effects could not be generalized by antibiotic class, outer membrane traverse mechanism, molecular weight, or the bactericidal nature of each antibiotic tested.